Traces of terror : counter-terrorism law, policing, and race - Sentas, Victoria (Oxford : Oxford University Press, 2014)
Based on field work in Australia, this book investigates the effects of counter-terrorism law and policing on Muslim, Somali, Turkish Kurds and Sri Lankan Tamil communities. Drawing together in-depth interviews with members of Victoria Police and those who are being policed, participant observations of community forums, and a detailed investigation of government and police policy, legislation and case law, the author explains how processes of criminalisation and racialisation are sustained.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on February 28, 2014).
Keywords: Terrorism -- Prevention; Terrorism -- Prevention -- Law and legislation; Racism